1979
DOI: 10.1159/000275431
|View full text |Cite
|
Sign up to set email alerts
|

Menière’s Disease: Morphological Findings in Eighth Nerve and Vestibular End Organs

Abstract: 37 patients with advanced Menière’s disease were operated on by translabyrinthine 8th nerve neurectomy or middle fossa vestibular neurectomy. Cochlear and vestibular nerves, epithelia of the utricular macula and ampullar crista of horizontal canal were studied. All specimens were fairly well preserved and the microscopic studies suggested that there is no general deterioration of these structures even in long-standing, advanced Menière’s disease, but some minor deviations from normal are present in individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, this hypothesis was not supported by histological studies, in which observed changes were entirely different from those observed by one of the authors (JY) in the eighth nerve of patients with perilymphatic fistula. Changes in the case presented were also different from changes in the eighth nerve of patients with such otoneurological diseases as Meniere's (Ylikoski et al, 1979), vestibular neuronitis or sudden hearing loss with vertigo (Ylikoski et al, 1981). The patient's history revealed head traumas, and plain X-rays of the skull showed an old fracture line in the right parietal bone.…”
Section: Discussionmentioning
confidence: 68%
“…However, this hypothesis was not supported by histological studies, in which observed changes were entirely different from those observed by one of the authors (JY) in the eighth nerve of patients with perilymphatic fistula. Changes in the case presented were also different from changes in the eighth nerve of patients with such otoneurological diseases as Meniere's (Ylikoski et al, 1979), vestibular neuronitis or sudden hearing loss with vertigo (Ylikoski et al, 1981). The patient's history revealed head traumas, and plain X-rays of the skull showed an old fracture line in the right parietal bone.…”
Section: Discussionmentioning
confidence: 68%